Evaluation of Security Mechanisms for Information Dissemination in Wireless Sensor Networks - Mohamad Nazim, Jambli; Sinarwati, Mohamad Suhaili; Nurul Sahida, Mansor (IEEE, 2013)
In recent years, extensive research has been conducted on Wireless Sensor Networks (WSNs) due to their wide range of potential applications ranging from commercial to critical military and health care applications. For most of these applications, security is an important requirement. However, security mechanisms in WSNs differ from traditional ad-hoc networks due to their energy and resource constraints. Due to these constraints, the sensor nodes are vulnerable to security threats because the traditional security measures are not enough to protect these nodes during information dissemination in WSNs. Thus, in this paper we have studied TinySec security measures, Authentication-only (TinySec-Auth) and Authentication Encryption (TinySec-AE) in order to evaluate the suitability of these security measures for WSN applications. We have evaluated these TinySec mechanisms in terms of packet transmission time, average number of packet received and energy consumption. The simulation results show that TinySec-AE consumed more energy and required more time to transmit packet in comparing to TinySec-Auth due to higher computational time and longer packet size for extra encryption mechanism.